Effects of very low blood lead levels on neurobehavioral performances of male policemen in kota Bharu, Kelantan - Nordin, Rusli; Naing, Lin; Sadiq, Mohd Ayub (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2003)
Many published studies that examined the effect of lead exposur~ on neurobehavioral performances were conducted in confined manufacturing environment with low to moderate blood lead levels as a marker of exposure. This study was conducted in a general environmental setting with very low exposure intensity and blood lead levels. The objective of the study was to determine the effect of very low blood lead levels (below 10 J.Lg/dl) on the neurobehavioral performances of policemen in Kota Bharu, Kelantan. The study was cross-sectional in design and comprised of 89 policemen working in Kota Bharu district. The lead concentration of venous blood was determined . using graphite furnace absorption spectrometer. "-We assessed neurobehavioral performances using fh:e WHO Neurobehavioral Core Test Battery (NCTB). The mean blood lead concentr~tion was 2.5 ± 1.0 J.Lg/dl. Among the seven tests performed, the positive effect o~ blood lead on Benton visual retention was not significant after controlling for th~ confounding effect of smoke-dose. This study suggested that very low blood lead levels have no significant effects on the neurobehavioral performances. Therefore, more studies with blood lead levels below the recommended environmental limit of 10 J.Lg/dl, as recommended by the Centers for Disease Control (CDC), be conducted in order to justify that limit.